THE EFFECT OF FINANCIAL PERFORMANCE ON STOCK RETURNS OF PROPERTY & REAL ESTATE COMPANIES LISTED ON THE IDX IN 2020-2021 (Accounting Study Program, Universitas Ciputra Surabaya, 2022)
Abstract: This research aims to analyze the effect of financial performance on stock returns of property & real estate companies listed on the Indonesia Stock Exchange in 2020 - 2021. The research method used is quantitative descriptive which is carried out by collecting and analyzing quantitative data and statistical testing, as well as the type of causal conclusive research. The analytical technique used in this research is Multiple Linear Regression Analysis, t-test, and F-test. The sampling technique used is non-probability sampling, namely the purposive sampling method. The independent variable used in this research is financial performance. Financial performance is meant here is financial performance measured using financial ratios, namely Earning Per Share (EPS), Return on Equity (ROE), and Net Profit Margin (NPM) variables, while the dependent variable is Stock Return. The sample in this research is 47 property & real estate companies that have been listed on the IDX in the period 2020 - 2021 and have complied with the research criteria made. The research method used is Multiple Regression, CAPM & Simple Regression obtained using SPSS. The results of the study indicate that the EPS and ROE variables have no significant effect on stock returns, NPM has a significant effect on stock returns, and CAPM has no significant effect on stock returns. Keywords: Financial Performance, EPS, ROE, NPM, CAPM, Stock Return.